Study of the drying of mesocarp of baru (Dipteryx alata Vogel) fruits - Pâmella M. de Oliveira; Daniel E. C. de Oliveira; Osvaldo Resende; Daiana V. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Baru (Dipteryx alata Vogel) is a tree species that is part of the group of native species of the Cerrado and occurs mainly in Central Brazil, being valued for its various uses. Thus, the present work was carried out with the objective of studying the kinetics of drying of the mesocarp of baru fruits, performing the analysis of the thermodynamic properties, as well as evaluating the effect of drying on the color of the flour produced from the mesocarp. The mesocarp of baru fruits was placed in stainless steel trays, and dried at 40, 50, 60 and 70 ºC in a forced circulation oven until the moisture content of 0.12 dry basis (d.b.) was reached. Subsequently, the experimental data of the drying were adjusted with the mathematical models frequently used, and color was evaluated after the drying. It is concluded that the Wang & Singh model was selected to represent the drying curves of the baru mesocarp. For the thermodynamic properties, with increasing drying air temperature, the entropy and enthalpy values decreased while the Gibbs free energy increased. Regarding color, the results showed that with the increase of drying air temperature, there is a change in color, which indicates loss in the qualitative aspect.